Non Registered Trade Sector and Fiscal Mobilization in Developing Countries: Case Study of African Countries South of the Sahara (ACSS) - (:unkn) unknown (My University, 2009)
Budget crises which are among others, consequences of a low level of internal resources, have increased in ACSS, namely with the increasing development of what is generally known as Non Registered trade or underground economy. This plan of economic activities which have been regrouped within the non registered trade sector is made up of a set of traders (big and small) who are operating in a "bit fishy" way, because they work outside measures and regulations in terms of taxation. The fraudulent sector, which is an essential component of the non registered trade sector, is exercising pressures on fiscal mobilization in many ways. These strategies range from patently "wrong" declaration of the real level of activities, to the irregular transfer of taxes and excises collected or not, and on behalf of the Government. This sector is an important fiscal centre which unfortunately for both social and political reasons, sometimes bears fiscal charges beyond its real contributory capacities. On the other hand, our analysis has highlighted the fact that contrary to the largely wide-spread opinion, the presence of the informal trade sector does not significantly affect fiscal mobilisation. Indeed, the latter pays its direct taxes through the payment of trading dues; it also bears the indirect taxes through fiscal persistence, taxes which are generally paid during its demand in raw commodities. This trade sector is a poor source on which one can hope, in terms of fiscal mobilisation, much more than what has already been collected. Thus, this thesis aims at highlighting the efforts of the non registered trade sector on fiscal mobilisation in the African Countries South of the Sahara, together with the channels through which its effects are perceived. Strategies proposals aiming at a better control of the non registered trade sector have been developed in the last chapter.
Keywords: African Research